1999
DOI: 10.1046/j.1365-2133.1999.02975.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical maxacalcitol for the treatment of psoriasis vulgaris: a placebo-controlled, double-blind, dose-finding study with active comparator

Abstract: 1alpha, 25-Dihydroxy-22-oxacalcitriol (maxacalcitol) is a vitamin D3 analogue which displays approximately 10 times greater efficacy at suppressing keratinocyte proliferation in vitro than calcipotriol and tacalcitol. To determine clinical efficacy, a phase II double-blind, randomized, left vs. right, concentration-response study was performed with once-daily topical maxacalcitol in patients with mild to moderate chronic plaque psoriasis. Primary efficacy parameters were psoriasis severity index (PSI) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
5

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 3 publications
2
56
0
5
Order By: Relevance
“…Therefore, it is speculated that VitD3 derivatives may be useful for the therapy of Th1-dependent immune diseases. Indeed, recently, it has been reported that VitD3 derivative is effective against psoriasis in human and experimental autoimmune encephalomyelitis in animal models (4,5,18,23). However, the precise mechanism has remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is speculated that VitD3 derivatives may be useful for the therapy of Th1-dependent immune diseases. Indeed, recently, it has been reported that VitD3 derivative is effective against psoriasis in human and experimental autoimmune encephalomyelitis in animal models (4,5,18,23). However, the precise mechanism has remained unclear yet.…”
Section: Discussionmentioning
confidence: 99%
“…Psoriasis is an autoimmune disease, which is induced by abnormal acceleration of type-1 immune responses (14). Recently, it has been reported that topical 22-Oxa-1α,25-D 3 (maxacalcitol) is effective for the treatment of psoriasis (4,18). It remains unclear how VitD3 derivatives show their therapeutic effect against psoriasis.…”
Section: Discussionmentioning
confidence: 99%
“…OCT is the most used vitamin D3 analog in Japan, which displays approximately 10 times greater efficacy at suppressing keratinocyte proliferation in vitro compared with calcipotriol and tacalcitol. 20 We found that OCT significantly suppressed the expression of IL-4 and IL-13-induced POSTN in dermal fibroblasts. We hypothesize that decreased POSTN expression might be one of the mechanisms by which topical treatment with a vitamin D analog is effective in scleroderma, especially in LS.…”
Section: Introductionmentioning
confidence: 82%
“…Ennek magyarázata lehet, hogy az aktív Dvitamin gyorsítja a keratocyták differenciálódá sát és gátolja a proliferációjukat [47,48,49], ugyan akkor előnyösen hat a betegség kialakulásában szerepet játszó immunfolyamatokra is [50]. Napjainkban a be tegség egyik alapkezelése az ideális Dvitaminszint biztosítása mellett alkalmazott kalcitriol vagy a kevéssé hypercalcaemizáló Dvitaminanalógok (kalcipotriol, ta kalcitol, maxakalcitol) lokális használata [51,52,53,54,55,56,57].…”
Section: D-vitamin-hiány Hatása a Bőrre Dr Wikonkál Norbertunclassified